Policy plan "digital live" and implementation strategy online government national and territorial order for a better relationship between state and citizen (2014)
Through this paper aims to develop the policy of the government plan "Vive Digital" led by the Ministry of Information Technologies and Communications, know what your goal for the 2010-2014 quadrennium and the goals you have planned, also, to achieve the same aspirational make the inclusion of a digital Ecosystem, aimed at the expansion of infrastructure, creation of new services, applications and promotion of digital content, similarly, highlight the application component and the Government Online strategy , to learn about the regulations and agreements in contrast to the implementation that is intended for this plan of government, the strategy aims to improve the relationship between the state-citizens, progress, achievements implemented by Government Online initiatives and the impact on citizen participation.